2018
DOI: 10.1021/acs.jpca.8b05393
|View full text |Cite
|
Sign up to set email alerts
|

Superficial and Fundamental Correspondences in the Terahertz/IR (6–15 THz) Absorption Spectra of Aspirin and Benzoic Acid

Abstract: The terahertz absorption spectra of aspirin and benzoic acid have been measured in the range 200-500 cm (6-15 THz). Density-functional theory (DFT) modeling has assigned fundamental vibrational modes to the observed absorption bands. Hydrogen bonds between the crystalline planes of aspirin resulted in better agreement between the experimental and modeled spectra than for benzoic acid. The similar structure of these two molecules suggests a similar absorption spectrum, which indeed was obtained experimentally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…DFT theoretical calculations have been over years used in the interpretation of the THz spectra of materials and have proven to be a very successful technique for assigning the vibrational modes to experimental absorption peaks. 11,3436 We obtained a maximum deviation between DFT calculation and the experimental values of the peak energies as 15 cm –1 (0.45 THz), which is well within the error estimate of Orca calculations. It was observed that despite a good agreement between the theoretical and experimental energies, there is a mismatch in the intensities.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…DFT theoretical calculations have been over years used in the interpretation of the THz spectra of materials and have proven to be a very successful technique for assigning the vibrational modes to experimental absorption peaks. 11,3436 We obtained a maximum deviation between DFT calculation and the experimental values of the peak energies as 15 cm –1 (0.45 THz), which is well within the error estimate of Orca calculations. It was observed that despite a good agreement between the theoretical and experimental energies, there is a mismatch in the intensities.…”
Section: Resultssupporting
confidence: 81%
“…This sparsely studied THz frequency range is accessible using the conventional Fourier transform infrared (FT-IR) technique. The few studies that exist have however revealed characteristic absorption peaks in this frequency range 11,12 which can be used to identify or even characterize materials. The studied 6–15 THz region lies within the frequency range that is often also called far-infrared (FIR) range.…”
Section: Introductionmentioning
confidence: 99%
“…Its corresponding theoretical line was obtained at 220 cm −1 and it is also confirmed by modeling of the BA crystal with another method. 45…”
Section: Resultsmentioning
confidence: 99%
“…Similar conclusion was obtained earlier when comparing the modes of aspirin and BA. 45 This implies that each absorption band of terra preta samples cannot be necessarily assigned to one particular vibrational mode of the aromatic compounds these samples contain.…”
Section: Resultsmentioning
confidence: 99%
“…During the past few decades, the THz spectroscopy technique has been used to analyze wide range of substancesfrom DNA, [19] over explosive materials to several active pharmaceutical ingredients (API). [20][21][22][23][24] The spectrum in THz region of electromagnetic radiation (sub 200 cm À 1 ) provides information about low energy vibrational modes, which arise from interactions based on both intra-and inter-molecular characters. [25] Despite the fact that covalent intramolecular interactions are much stronger than hydrogen bonds or any other dispersion forces, intermolecular interactions characterize overall three-dimensional structure of a system.…”
Section: Introductionmentioning
confidence: 99%